Effectiveness Of National Health Insurance Policy Implementation On Access To Primary Health Care In Remote Areas - Retni, Retni (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
This study aims to analyze and understand the themes and trends in the literature related to primary health care using bibliometric analysis techniques through VOSviewer. The main focus is to identify key issues such as access to primary health care services, chronic disease management, socioeconomic factors, and the use of technology in healthcare services. The findings indicate that universal access to effective health services requires an integration of social health determinants, adequate health workforce education, and technological innovation. These insights provide valuable guidance for policymakers and health practitioners to formulate more holistic and integrated strategies in improving the quality of primary health care services.